2017
DOI: 10.5999/aps.2017.44.4.319
|View full text |Cite|
|
Sign up to set email alerts
|

Reconstruction of Large Facial Defects via Excision of Skin Cancer Using Two or More Regional Flaps

Abstract: BackgroundFree-flap surgery and skin grafting can be used to reconstruct large facial defects that may result after skin cancer removal by Mohs micrographic surgery (MMS). However, these two methods may produce low postsurgical patient satisfaction with aesthetics, and free-flap surgery may produce an undue burden for the majority of skin cancer patients, who are of advanced age. Hence, the authors examined outcomes of large facial defect reconstruction using multiple flaps. MethodsAmong patients undergoing MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…If large defects are reconstructed with a single flap, increased tension would arise during closure of the donor site; hence, wound dehiscence or hypertrophic scar formation may occur. If the defects are not closed, contractures or large scar formations may occur due to secondary healing or use of skin grafts [ 14 ]. Santos Stahl et al [ 15 ] and Little et al [ 16 ] reported an approximately 5% increase in the rate of skin necrosis after a forehead flap.…”
Section: Discussionmentioning
confidence: 99%
“…If large defects are reconstructed with a single flap, increased tension would arise during closure of the donor site; hence, wound dehiscence or hypertrophic scar formation may occur. If the defects are not closed, contractures or large scar formations may occur due to secondary healing or use of skin grafts [ 14 ]. Santos Stahl et al [ 15 ] and Little et al [ 16 ] reported an approximately 5% increase in the rate of skin necrosis after a forehead flap.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of cotton is regular to repel pathogens from the bloodstream. 28,29 Hence, the idea of utilizing anti-malignant agents on cotton fiber will diminish the reactions and harms. Despite the wide utilization of LS in numerous industrial creations, this is the first run through to utilize it as malignancy hopeful medication.…”
Section: Introductionmentioning
confidence: 99%